2021
DOI: 10.1002/osp4.514
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, diet, and weight loss in patients recruited from primary care settings: An update on obesity management interventions

Abstract: Background: Obesity and related comorbidities are the most common chronic conditions in North America where behavior modification including the adoption of physical activity (PA) and a healthful diet are primary treatment strategies. Patients are more likely to engage in behavior modification if encouraged by their physician; however, behavioral counseling in primary care rarely occurs due to lack of training and resources. A more effective method may be to refer patients from clinical settings to other health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Interventions to increase physical activity should limit their focus on weight management, as it can make individuals feel that physical activity is not improving their health if they are not losing weight [ 42 ]. Interventions should focus on the fact that independent of weight, physical activity is a good activity for everybody [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interventions to increase physical activity should limit their focus on weight management, as it can make individuals feel that physical activity is not improving their health if they are not losing weight [ 42 ]. Interventions should focus on the fact that independent of weight, physical activity is a good activity for everybody [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…This translational gap is unsurprising given a health care system whose payment models are misaligned for supporting lifestyle interventions, a medical workforce that lacks training on delivering lifestyle-based treatment, and weak public health infrastructure for community intervention delivery. Without major health system reform, as well as sustained investment to facilitate intervention delivery that approximates the fidelity seen in clinical trials, translating lifestyle interventions into real-world settings will continue to produce modest results [5,6].…”
Section: Behavioral Approaches Do Not Produce Lasting Weight Loss For...mentioning
confidence: 99%
“…Lifestyle modification programs can be implemented in many venues e.g., specialized obesity clinics, primary care, commercial, private dietetics practice or academic medical centers [13][14][15][16]. Typically, these programs induce modest WL that results in significant improvement in obesity-associated health conditions (sleep apnea, T2D, hypertension, hyperlipidemia) as well as positive psycho-social effects (mood, quality of life, body image) [17,18]. Several studies have demonstrated the efficacy of life style modification in promoting WL and improving obesity-associated comorbidities.…”
Section: Lifestyle Modificationmentioning
confidence: 99%